Assessing the Development and Forms of Continuous Evaluation Methods Employed in Interdisciplinary Science and Social Studies with LUMI Education - Triana, Hana; Maksum, Arifin; Nurhasanah, Nina (Pascasarjana UM, 2023)
The aim of this study was to evaluate the efficacy of interactive applications in primary education settings, focusing on continuous assessment practices and the overall performance of teaching Science and Social Studies. A descriptive-comparative research methodology was employed in this investigation. The participants comprised fifteen Grade 4 Cambridge students.The findings revealed that the content utilized for ongoing assessment through interactive applications encompassed information on Earth features, human interaction, and plant-based natural resources. A crucial aspect of evaluating fundamental learning competencies predominantly involved describing, identifying, listing, naming, relating, and explaining concepts within the domains of social studies and science. The interactive approaches to continuous assessment received strong endorsement from the respondents, who found the applications engaging and enjoyable, leading to increased motivation, collaboration, and interest, ultimately resulting in improved academic performance. The individual mean scores for each student indicated a comprehensive understanding of Earth features, human interactions, and natural resources (plants). An action plan was proposed to enhance the effectiveness of Lumi Education Apps in fostering interdisciplinary learning in science and social studies. Furthermore, the study recommends that educators explore the expansion of interactive types of ongoing assessment utilizing Lumi Education Apps.